Credit Management. - Bullivant, Glen (Ashgate Pub., 2010)
The best single-volume guide for anyone responsible for managing credit, risk and customers. Previously published as Credit Management Handbook, the new edition, the new edition with a new editor has been revised to reflect changes in practice and technology and is the set text for the Institute of Credit Management (ICM) examinations.